Physical mechanisms responsible for the water‐induced degradation of PC61BM P3HT photovoltaic thin films. Issue 2 (30th September 2015) - Parnell, Andrew J.; Cadby, Ashley J.; Dunbar, Alan D. F.; Roberts, George L.; Plumridge, Alex; Dalgliesh, Robert M.; Skoda, Maximilian W. A.; Jones, Richard A. L.
ABSTRACT: We show that [6, 6]‐phenyl‐C61‐butyric acid methyl ester (PC61 BM) at the surface of thin film blends of poly(3‐hexylthiophene) (P3HT):PC61 BM can be patterned by water. Using a series of heating and cooling steps, water droplets condense onto the blend film surface. This is possible due to the liquid‐like, water swollen layer of poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate. Breath pattern water deformation and subsequent drying on the film surface results in isolated PC61 BM structures, showing that migration of PC61 BM takes place. This was confirmed by selective wavelength illumination to spatially map the photoluminescence from the P3HT and PC61 BM. Within a device, redistribution of the surface PC61 BM into aggregates would be catastrophic, as it would markedly alter device performance. We also postulate that repeated volume change of the poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate layer by water swelling may be, in part, responsible for the delamination failure mechanism in thin film solar cells devices. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2016, 54, 141–146 Abstract : The water‐induced degradation mechanisms in polymer and hybrid polymer solar cells are explored by simulating the heating and cooling cycles that may be experienced during their operation. The surface distribution of PC61 BM can be markedly altered from a planar uniform distribution by the presence of water, as breath pattern type structures are readily formed on the surface. These surface indentations are made possible by the liquid‐like swollen nature of the poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate layer.